(untitled) (Research, Society and Development, 2024)
The management of Urban Solid Waste in Brazil shows that this approach has a multidimensional character, in view of the involvement of issues related to the environment, economy, culture and social issues, which are seen as waste that is not used. The objective of this study was constructed To report facts about the group of women focusing on solid waste in the municipality of Magalhães Barata in the state of Pará, Brazil. The methodology of this study refers to an ex-post-facto research of a descriptive nature with a qualitative and quantitative approach. Results: in this construction, 17 publications and 4 books of scientific methodology were identified, in which the data were systematized and then the textual body of these studies was constructed. Final considerations: It is observed that the municipality of Magalhães Barata/PA, should create stricter laws regarding the disposal of Urban Solid Waste – MSW. Thus, with the use of digital technology and environmental education for citizens, they would be economically viable actions that can contribute to the mitigation of an environmentally appropriate final disposal of MSW generation.